Perceptions of English and Literature Department Students on Lecturer’s Feedback for Critical Book Review (CBR) - Bahagia Saragih; Anggraini Thesisia Saragih; Ade Aini Nuran; Ade Farida Hanim Saragih; Muhammad Natsir (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to analyze Perceptions of English and Literature Department Students perceptions on lecturer’s feedback for Critical Book Review (CBR). A descriptive qualitative design was used in this study. The data sources are all students outside the English Education study program who take 5 courses, namely Curriculum and Textbook Analysis, Translation in Language Teaching, English Culture in ELT, Technology in ELT and Management of English Based Institution. The data are the results of questionnaires given to students outside the Study Program who are conducting the student exchange program (Permata). Research shows that students feel helped by the feedback provided by the lecturer in the form of corrections, criticisms, suggestions, and providing solutions either orally or in writing. The reason why lecturers provide feedback is to measure students' abilities in doing CBR assignments.